Optimal factor and commodity taxation in a small open economy - Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
A two-sector trade model with perfect international capital mobility and endogenous supply of specific factors is used to analyze the relation between selective taxes on production (origin-based commodity taxes) and source-based taxes on capital income. A small open economy will set both of these taxes equal to zero when it is able to tax all specific factors optimally. In the absence of a domestic motive for capital taxation a switch towards origin-based commodity taxes leads to a negative source tax on capital (i.e., a subsidy). However, when one of the specific factors is in fixed supply and cannot be taxed by a separate instrument, then the optimal capital tax rate is positive and may be further increased by the introduction of a selective production tax.
Keywords: 330